PENGEMBANGAN TES KOGNITIF BERBASIS REVISI TAKSONOMI BLOOM PADA MATERI SISTEMREPRODUKSI UNTUK SISWA SMA - Taufiq, Ainul Uyuni (Jurnal Biotek, 2015)
This study aims to determine the quality of the test device was developed. In terms of the quality of test validity, reliability, difficulty level , determinant indeks, and effectiveness of distractors. This study used a qualitative approach to the development of research methods. Development of procedures to implement the software development model 4-D which consists of phases define, design, develop and dessiminate. The data were obtained through two criteria: (1) the validity of the data obtained through experts assessment, (2) item validity data, reliability, difficulty level , determinant indeks, and effectiveness of distractors obtained through the test results of cognitive tests. Validity of the data obtained was analyzed mathematically and categorized based on the standards set, while item validity data, reliability, difficulty level, determinant indeks, and effectiveness of distractors analyzed with the help of Microsoft Excel 2007. Validation results showed that cognitive tests have very valid category with a value of 3.54 based on experts assessment. The next conducted trials to determine the quality of the cognitive tests. In terms of item validity, valid category (92% for type A, 92% for type B), not valid (8% for type A, 8% for type B). In terms of reliability, including in the category of reliable with values about 0,71 for type A and 0,74 for type B. In terms of difficulty level, easy category (30% for type A, 22% for type B), medium category (48% for type A, 65% for type B), difficult category (22% for type A, 13% for type B) . Determinant indeks, poor category (9% type A, 4% type B), satisfactory (35% type A, 31% type B), good (52% type A, 61% type B), excellent (4% type A, 4% type B). Effectiveness of distractors, effective category (87% type A, 91% type B), not effective category (13% type A, 9% type B)